Soil aeration and liming in Esmeralda zoysiagrass sports turf - Ferreira dos Santos, Patrick Luan; Leal do Nascimento, Mateus Vinícios; Costa, João Victor; Lelles Moreira Begueline, Maria Clara; Villas Bôas, Roberto Lyra; Grava de Godoy, Leandro José (Revista Agrogeoambiental, 2026)
Esmeralda zoysiagrass is the most widely marketed among turfgrass species; however, the soil’s chemical and physical factors can interfere with its development. Thus, it is essential to seek alternatives to mitigate these effects, and the combined use of liming and soil aeration may be an option. This study aimed to evaluate the impact of soil aeration combined with liming on Esmeralda grass. The experiment was conducted from November 14, 2018, to May 30, 2019, in a 363 m² experimental area divided into 30 plots. A randomized block design was used, consisting of five treatments with six replications: T1 – without liming and without aeration; T2 – without liming and with aeration; T3 – with liming and without aeration; T4 – with liming and aeration after liming; and T5 – with liming and aeration before liming. The following parameters were evaluated: soil plant analysis development meter (SPAD); height; dry mass of clippings; root length; dry mass of roots + rhizomes + stolons; and traction resistance. The best results were obtained from treatments combining liming with solid tine aeration (T4 and T5), demonstrating that this practice can be an excellent management strategy for the development of Esmeralda grass in sports fields.